PENGARUH VARIASI KONSENTRASI MINYAK ZAITUN (OLIVE OIL) TERHADAP KELEMBUTAN SABUN CAIR - Mikhania Christiningtyas Eryani, Dewi Rashati (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2016)
Zaitun tree (Olea europaea) comes from the Middle East and widely grown in Asia. The fruit and oil extraction widely used as food and medicine. The oil derived from olives is known as olive oil. Olive oil can be used for skin emolient. The aims of this study was to determine olive oil variation concentration to liquid soap softness. The soap was made with varying olive oil concentration (20% known as F1, 30% known as F2 and 40% known as F3). True experimental design with The Posttest Only Experiment was used as the study design. Evaluation of the soap including organoleptic test, pH, spesific gravity, free alkali assay, and responden emolient test. Responden emolient test was taken from 20 responden who has given questioner. The data from emolient test study was calculate by Kruskal Wallis test. The organoleptic test result showed that all formula showed liquid green, homogen, and jasmine odor. pH from F1, F2 and F3 were 10,39; 9,75 dan 9,34 respectively. The spesicic gravity from F1, F2 and F3 were 1,648%; 1,441% dan 0,863 % respectively. The free alkali from F1, F2 and F3 were 0,032%; 0,08% dan 0,064% respectively. The responden emolient test showed that F1 was soft, F2 was midle soft and F3 was very soft.Keywords: oilive oil, soap, softness